Downregulation of miR-135b-5p Suppresses Progression of Esophageal Cancer and Contributes to the Effect of Cisplatin - Di, Yuzhu; Jiang, Yanan; Shen, Xiuyun; Liu, Jing; Gao, Yang; Cai, Huimin; Sun, Xiaoli; Ning, Dandan; Liu, Bing; Lei, Jiaji; Jin, Shizhu (Frontiers in Oncology, 2021)
Esophageal cancer (EC) is one of the commonest human cancers, which accompany high morbidity. MicroRNAs (miRNAs) play a pivotal role in various cancers, including EC. Our research aimed to reveal the function and mechanism of miR-135b-5p. Our research identified that miR-135b-5p was elevated in EC samples from TCGA database. Correspondingly real-time PCR assay also showed the miR-135b-5p is also higher expressed in Eca109, EC9706, KYSE150 cells than normal esophageal epithelial cells (Het-1A). CCK8, Edu, wound healing, Transwell assay, and western blot demonstrated miR-135b-5p inhibition suppresses proliferation, invasion, migration and promoted the apoptosis in Eca109 and EC9706 cells. Moreover, the miR-135b-5p inhibition also inhibited xenograft lump growth. We then predicted the complementary gene of miR-135b-5p using miRTarBase, TargetScan, and DIANA-microT. TXNIP was estimated as a complementary gene for miR-135b-5p. Luciferase report assay verified the direct binding site for miR-135b-5p and TXNIP. Real-time PCR and western blot assays showed that the inhibition of miR-135b-5p remarkably enhanced the levels of TXNIP in Eca109 and EC9706 cells. Furthermore, cisplatin (cis-diamminedichloroplatinum II, DDP) decreased miR-135b-5p expression and increased TXNIP expression. Enhanced expression of miR-135b-5p attenuated the inhibitory ability of cisplatin (cis-diamminedichloroplatinum II, DDP) in Eca109 cells, accompanied by TXNIP downregulation. In conclusion, the downregulation of miR-135b-5p suppresses the progression of EC through targeting TXNIP. MiR-135b-5p/TXNIP pathway contributes to the anti-tumor effect of DDP. These findings may provide new insight into the treatment of EC.